Food system transformation for sustainable city-regions: exploring the potential of circular economies. Issue 12 (2nd December 2022) - Lever, John; Sonnino, Roberta
ABSTRACT: Calls for food system transformation to strengthen synergies between socio-economic and environmental goals have been growing in recent years. As yet, however, insights from theoretical debates have not been tested against the actions and perceptions of food system actors. To add empirical weight to this debate, we focus on a region in the north of England where the Covid-19 crisis has challenged the embeddedness of linear thinking and siloed policy approaches. Based on an exploration of the potential of 'circular food economies', the analysis provides insights into the capacity of 'city-regions' to reorientate food system dynamics towards sustainability objectives.